The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1516-44462009005000015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoxetine and imipramine in rat fetuses treated during a critical gestational period: a macro and microscopic study

Abstract: OBJECTIVE: To evaluate morphological alterations in rat fetuses treated with fluoxetine and imipramine during the "critical" period of gestation. METHOD: Fifteen female rats were separated into three groups (n = 5) and treated with 10 mg/kg/day of test substances on the ninth, tenth and eleventh day of pregnancy: G1, fluoxetine; G2, imipramine hydrochloride; G3 (control), saline. On day 21, cesarean sections were performed to release the fetuses, whose bodies were weighed and macroscopically analyzed. The plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Additionally, studies in women suggest that antidepressant doses need to be increased to maintain euthymia during the second half of pregnancy (Hostetter et al, 2000; Sit et al, 2008), due to increased drug metabolism (Sit et al, 2008). Similar to the present findings, there are also previous reports of peri- and postnatal complications from antidepressant drug treatment during late pregnancy in rodents (Swerts et al, 2009; Van den Hove et al, 2008). However, in humans the primary adverse outcome of SSRI exposure during pregnancy appears to be preterm birth, which may also result from untreated depression (Bigos et al, 2009; Wisner et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, studies in women suggest that antidepressant doses need to be increased to maintain euthymia during the second half of pregnancy (Hostetter et al, 2000; Sit et al, 2008), due to increased drug metabolism (Sit et al, 2008). Similar to the present findings, there are also previous reports of peri- and postnatal complications from antidepressant drug treatment during late pregnancy in rodents (Swerts et al, 2009; Van den Hove et al, 2008). However, in humans the primary adverse outcome of SSRI exposure during pregnancy appears to be preterm birth, which may also result from untreated depression (Bigos et al, 2009; Wisner et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Changes in birth weight or growth attributed to prenatal NRI exposure have been reported in the clinical literature. Animal studies show conflicting results; some report no changes in pup weight or litter size (Rodríguez Echandía and Broitman, 1983;De Ceballos et al, 1985b;Harmon et al, 1986;Stewart et al, 1998), an increase in fetal and neonatal weights (Cuomo et al, 1984;Swerts et al, 2010), or reduced birth weight in pups and reduced …”
Section: Selective Serotonin Reuptake Inhibitor Antidepressant Animentioning
confidence: 99%
“…It should also be noted that most preclinical research with regards to the effects of perinatal antidepressant medication exposure on neurobehavioral outcomes has investigated the effects of these antidepressant medications on offspring of healthy mothers [13,38,39,40,43]. However, because the primary action of antidepressant medications is to alleviate depressive symptoms, more preclinical research is needed on the impact of SSRIs on development in offspring subject to maternal adversity.…”
Section: Perinatal Exposure To Ssris and Neural Development: Preclinimentioning
confidence: 99%
“…Research on the effect of SSRIs on brain development in rats has shown that fluoxetine treatment during gestation days (GD) 9–11 has no effect on fetal encephalic weight or the number of neurons in the frontal lobe at GD21 [43]. In contrast, treatment with imipramine, a tricyclic antidepressant, at the same time period during gestation, increases fetal brain weight and decreases neuron number in the frontal lobe of the fetal rat encephala at GD21 [43].…”
Section: Preclinical Studies On Perinatal Ssri Effects In the Absencementioning
confidence: 99%
See 1 more Smart Citation